Peningkatan Kualitas Hidup Pasien Tuberkulosis dengan Pemantauan Peran Pengawas Minum Obat (PMO) - Lily Putri Marito; Siti Zahara Nasution; Fajrinur Syarani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the relationship between the role of drug supervisors (PMOs) on improving the quality of life of tuberculosis patients. This research method is quantitative research with correlation research design with a sample of 40 tuberculosis patients. The sampling technique used purposive sampling according to the inclusion criteria. Data analysis used Chi-Square test. The results showed that 29 people (72.5%) had an active PMO role. The majority of quality of life based on aspects obtained in poor physical health is 33 people (82.5%) and the overall quality of life is good as many as 26 people (65%). Chi-Square statistical test results with an Asym.Sig value of 0.034 <0.05 means that there is a significant relationship between the role of PMO and quality of life. In conclusion, PMO has a very important role in the process of treating TB patients regularly so as to improve the health status and quality of life of patients. Keywords: Quality of Life, Drug Supervisor (PMO), Tuberculosis